Biotechnology in Drug Delivery: Evolution, Obstacles and Applications - KAMLESH WADHER,; RAVI KALSAIT,; DR. MILIND UMEKAR, (International Journal of Pharma and Bio Sciences, 2010)
Biotechnology is the application of biology to the development of products and services that use naturally occurring molecules created to restore biologic processes. In simple language it uses or modifies the living things for human purposes. Biotechnology has evolved dramatically during the past 50 years, beginning with the discovery of deoxyribonucleic acid. Biotechnical methods are now used to produce many proteins for pharmaceutical and other specialized purposes Gene therapy – altering DNA within cells in an organism to treat or cure a disease – is one of the most promising areas of biotechnology research. New genetic therapies are being developed to treat diseases such as cystic fibrosis, AIDS and cancer. The biggest challenge in the preclinical assessment of biotech products has been coping with species specificity and the associated detection and implications of altered immune status and unpredicted pleiotropic activity.Over the next two decades, discoveries in biotechnology and advances in gene therapy will transform the practice of medicine. The idea of merging biological and nonbiological systems at the nanoscale level is not a new one. The broad field of bioconjugate chemistry is based on combining the functionalities of biomolecules and nonbiologically derived molecular species for specialized use in applications Gene therapy and RNAi technologies are considered the medical treatments of the future.